Motif Viewers dalam Menonton Review Fashion pada Youtube - Taufiqul Qoffar Qoniyyul Bakhri; Laili Zulfa (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
This study aims to identify and analyze viewers' motives in watching fashion review content on the YouTube platform. The study was conducted in Semarang City during the period from October 1 to October 31, 2025 with a qualitative approach. Data collection techniques include documentation and observation of audience behavior and the content displayed. The results showed that the main motives of viewers included searching for product references, obtaining tips and guides, comparing products, as well as social validation and credibility from reviewers. In addition to the informative aspect, the entertainment dimension is also a significant factor that drives interest in watching. Psychological satisfaction such as pleasure, relaxation, and emotional fulfillment become part of the viewing experience, especially when filling your free time. Viewers also show interest in the vlogger's personality, communicative delivery style, and visually appealing video production quality. The aesthetic pleasure of creatively packaged fashion looks also strengthens the appeal of the content. These findings suggest that the motivation for watching is not only functional but also emotional and aesthetic. The implications of this study can be input for fashion content creators in designing more effective and attractive delivery strategies, as well as for fashion industry players to understand the behavior of digital consumers in accessing product information through social media.